تعزيز شفافية افصاح سلاسل التوريد باستخدام تطبيقات بلوك تشين (دليل من الشركات الأمريكية المدرجة ببورصة Nyse) - بخاوة محمد الأمين; طيبي حمزة (جامعة الوادي University Of Eloued, 2024)
This study aimed to test and measure the effect of using blockchain technology in enhancing the transparency of disclosure of supply chains, as well as assessing the relationship before and after the use of Blockchain, in order to provide practical evidence in the context of listed firms in NYSE, to achieve this, The data was collected and analyzed by using content analyses of annual financial reports (k-10), for a sample of 16 listed firms, during the period from 2017 to 2022, with a total of 96 observations, the results of the study show significant positive effect of using blockchain in enhancing the transparency of disclosure of supply chains, which confirms a positive relationship, and this effect differs substantially for periods after use and the periods before use, which was different with the stability of the effect depending on each of the control variables (firm size, LEV, and ROA), the results of which were not significant. It recommended the necessity of constantly monitoring and evaluating the effectiveness of implementing to ensure the process of continuous improvement, and making the necessary adjustments to ensure that the benefits and gains of use are realized
Enhancing supply chain disclosure transparency using Blockchain applications (Evidence from US-listed firms in NYSE)
Keywords: بلوك تشين; شفافية الافصاح; سلاسل التوريد; بورصة نيويورك; blockchain; disclosure transparency; supply chain; NYSE